Talent is overrated what really separates world-class performers from everybody else - Colvin, Geoffrey (New York Portfolio, 2008)
Asked to explain why a few people truly excel, most people offer one of two answers. The first is hard work. Yet we all know plenty of hard workers who have been doing the same job for years or decades without becoming great. The other possibility is that the elite possess an innate talent for excelling in their field. We assume that Mozart was born with an astounding gift for music, and Warren Buffett carries a gene for brilliant investing. The trouble is, scientific evidence doesn't support the notion that specific natural talents make great performers.
Includes bibliographical references (p. 209-219) and index.
Keywords: Work--Psychological aspects